(untitled) (Medico Legal Update, 2020)
Objective: To determine the risk factors for cardiovascular disease among patients with type 2 diabetes. Methods: The data were collected by utilization of the study instruments and employment of scheduled interview as means data collection. The data collection process was performed from July 2nd / 2019 / October 2nd/ 2019. A questionnaire was designed constructed by the researcher to measure the variable .The questionnaire consisted of3 parts which are demographical, clinical information and risk factors. The reliability of the questionnaire was determined through a pilot study and the validity through a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which include Pearson correlation coefficient, and contingency coefficient. Results: Results: The result of the study showed that the most common modifiable risk factors were low HDL-C levels (69%), smoking (40%), hypertension (46%), Overweight (57%), high triglycerides (21%), hypercholesterolemia (15%), and high LDLC (12%). All these factors were positively and significantly associated with the development of CVD. Whereas, the most common non-modifiable risk factors were age 50 years and more, sex, family history of CVD .